2017
DOI: 10.1002/anie.201708421
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bithiophene Imide Fusion on the Device Performance of Organic Thin‐Film Transistors and All‐Polymer Solar Cells

Yingfeng Wang,
Zhenglong Yan,
Han Guo
et al.

Abstract: Two new bithiophene imide (BTI)-based n-type polymers were synthesized. f-BTI2-FT based on a fused BTI dimer showed a smaller band gap, a lower LUMO, and higher crystallinity than s-BTI2-FT containing a BTI dimer connected through a single bond. s-BTI2-FT exhibited a remarkable electron mobility of 0.82 cm V s , and f-BTI2-FT showed a further improved mobility of 1.13 cm V s in transistors. When blended with the polymer donor PTB7-Th, f-BTI2-FT-based all-polymer solar cells (all-PSCs) attained a PCE of 6.85 %,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
112
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(115 citation statements)
references
References 43 publications
(63 reference statements)
3
112
0
Order By: Relevance
“…[29,34] Furthermore, the conjugated length of backbone can precisely lessen the steric hindrance of the adjacent side chain to regulate the crystallinity and intermolecular π-π stacking, resulting in better polymer-small molecular acceptor miscibility and microstructures. [37] In this work, we report a new synthesis method of asymmetric building block TBD containing four fused rings with longer backbone length than BDT unit and shorter than DTBDT unit. [36] During the drying process of the active layer, the poly mer with high crystalline behavior will have a tendency to form large domain size, leading to terrible miscibility.…”
Section: Introductionmentioning
confidence: 99%
“…[29,34] Furthermore, the conjugated length of backbone can precisely lessen the steric hindrance of the adjacent side chain to regulate the crystallinity and intermolecular π-π stacking, resulting in better polymer-small molecular acceptor miscibility and microstructures. [37] In this work, we report a new synthesis method of asymmetric building block TBD containing four fused rings with longer backbone length than BDT unit and shorter than DTBDT unit. [36] During the drying process of the active layer, the poly mer with high crystalline behavior will have a tendency to form large domain size, leading to terrible miscibility.…”
Section: Introductionmentioning
confidence: 99%
“…

In recent years, n-type organic semiconductor (n-OS) (or called as nonfullerene) acceptors have been gaining their popularity in low production cost, light weight, flexible and large-area applications in polymer solar cells (PSCs) due to their excellent optical absorption, tunable energy levels, facile synthesis, and good solution-processability. [14,[17][18][19][20][21][22][23][24][25][26][27][28][29] And the n-OS acceptors-based devices have achieved power conversion efficiency (PCE) as high as over 12%. [14,[17][18][19][20][21][22][23][24][25][26][27][28][29] And the n-OS acceptors-based devices have achieved power conversion efficiency (PCE) as high as over 12%.

…”
mentioning
confidence: 99%
“…Cyclic voltammetry (CV) measurement was performed to determine the lowest unoccupied molcular orbital (LUMO) and highest occupied molcular orbital (HOMO) levels of s‐FBTI2‐FT (Figure a). The LUMO/HOMO levels were found to be −3.50/−6.08 eV, which are greatly lowered relative to those (−3.30/−5.82 eV, Table ) of s‐BTI2‐FT . The results indicate that F addition on the BTI core could enhance both the electron affinity and interchain packing of s‐FBTI2‐FT, showing the distinctive advantages of the fluorination.…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, the small E loss and FF of the s‐FBTI2‐FT cells demonstrated that there are great potentials for further PCE improvement. For the non‐fluorinated polymer s‐BTI2‐FT, the PTB7‐Th:s‐BTI2‐FT all‐PSCs exhibited very limited performance with a maximum PCE of ≈0.1% under various device fabrication conditions . The results clearly demonstrate that the fluorinated BTI‐based polymer s‐FBTI2‐FT is a promising acceptor for all‐PSCs and fluorination of acceptor moiety in the n‐type polymer is a highly effective strategy for improving the device performance.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation